Formation of conservative zones in the working environment at container vibration treatment - Калмыков, Михаил Александрович (Eastern-European Journal of Enterprise Technologies, 2012)
The geometrical questions of theory of vibrotreatment, related to the choice of the most acceptable configurations of container in cases trivial-parallel the external power field of excitation are considered. The analytical chart of decision of reverse task is resulted